Advancing Game Accessibility With Audio Description: User Perspectives and Recommendations - Larreina, María Eugenia; Mangiron, Carme (Journal of Audiovisual Translation, 2025)
Since 2020, game accessibility has gained significant attention from both industry and academia. For players with visual disabilities, features such as screen readers, sound cues, contrast settings and, more recently, audio description (AD) have been a game changer. In fact, research on game AD is still in its early stages, and more studies are needed to explore user needs and preferences. This paper examines AD as a crucial accessibility feature in games, beginning with a review of its current implementation, which primarily focuses on non-interactive game content. It then outlines findings from the Researching Audio Description: Translation, Delivery and New Scenarios (RAD) Project, specifically focusing on insights gathered from fifteen interviews with blind and low-vision adults in Spain. The interviews cover three topics: lack of game accessibility, potential features for AD in games, and next steps for improving game accessibility. Key interview results highlight the potential of incorporating AD into game design to improve access to non-interactive content. The paper concludes with ten guidelines addressed at developers, researchers, and other stakeholders to enhance game accessibility, stressing the importance of integrating accessibility at all stages of development in collaboration with players with disabilities. Lay summary Game accessibility means removing barriers that stop people, especially those with disabilities, from being able to play video games. In the past few years, the game industry and academia have shown a growing interest in game accessibility. Many games now offer accessibility features, such as screen readers, sound cues, contrast settings, and audio description (AD). AD is particularly useful for players who are blind or have low vision because it verbally narrates what is happening on the screen. However, despite these advances, there is still much work to be done. Research on how best to use AD in video games is still in its early stages, and more studies are needed to understand what blind and low vision players really want and need from AD in games. In this paper, we focus on the potential of AD as a key accessibility feature in video games. We start by reviewing how AD has been used in games so far. Our findings reveal that, while AD has been introduced in a few games, it is mostly limited to non-interactive content, like cutscenes. Then, we look at research projects about AD in video games, focusing on the RAD Project, in which we participated. This project gathered feedback from people with visual disabilities to learn about their experiences with AD and accessibility in video games. As part of this project, we interviewed 15 blind and low vision adults living in Spain. These interviews helped us understand their thoughts about game accessibility, with a focus on AD. Participants emphasized that AD should be built into the game from the start, not added later. They also felt that AD could greatly improve their gaming experience, especially by helping them understand game content that is not interactive. Based on these interviews and our review of current research, we created ten guidelines for developers, researchers, and other stakeholders involved in game accessibility. These guidelines encourage the inclusion of accessibility features throughout the entire game development process. They also stress how important it is to include people with disabilities when designing and testing games so that accessibility features work as intended. By following these guidelines, games can become more inclusive and enjoyable for everyone.